15-Deoxy-Δ(12,14)-prostaglandin J(2) inhibits multiple steps in the NF-κB signaling pathway - Straus, Daniel S. (The National Academy of Sciences, 2000)
Prostaglandin J(2) (PGJ(2)) and its metabolites Δ(12)-PGJ(2) and 15-deoxy-Δ(12,14)-PGJ(2) (15d-PGJ(2)) are naturally occurring derivatives of prostaglandin D(2) that have been suggested to exert antiinflammatory effects in vivo. 15d-PGJ(2) is a high-affinity ligand for the peroxisome proliferator-activated receptor γ (PPARγ) and has been demonstrated to inhibit the induction of inflammatory response genes, including inducible NO synthase and tumor necrosis factor α, in a PPARγ-dependent manner. We report here that 15d-PGJ(2) potently inhibits NF-κB-dependent transcription by two additional PPARγ-independent mechanisms. Several lines of evidence suggest that 15d-PGJ(2) directly inhibits NF-κB-dependent gene expression through covalent modifications of critical cysteine residues in IκB kinase and the DNA-binding domains of NF-κB subunits. These mechanisms act in combination to inhibit transactivation of the NF-κB target gene cyclooxygenase 2. Direct inhibition of NF-κB signaling by 15d-PGJ(2) may contribute to negative regulation of prostaglandin biosynthesis and inflammation, suggesting additional approaches to the development of antiinflammatory drugs.